WANPRESTASI PERUMAHAN SYARIAH NON-BANK: URGENSI STANDARDISASI LABEL ‘SYARIAH’ MELALUI SERTIFIKASI KEPATUHAN - Fadli Maulana (JOSH: Journal of Sharia, 2026)
The marketing of Sharia labeled housing by non bank developers has grown rapidly, yet the absence of binding standards and verification for the use of the Sharia label allows compliance claims to be made on a self declared basis, creating information asymmetry and contributing to widespread developer default and consumer losses. This article examines how the normative gap in standardizing and verifying Sharia labeling in non bank Islamic housing projects increases the risk of default and consumer vulnerability, and proposes a mandatory certification model as a preventive consumer protection instrument. Employing a normative legal method with statutory, conceptual, and case approaches, the study analyzes Indonesia’s consumer protection regime, the Halal Product Assurance framework, Sharia governance rules, and reported cases of default in non bank Sharia housing schemes. The findings indicate that, in practice, the Sharia label operates as a powerful compliance claim in marketing, but in the absence of enforceable auditing mechanisms it is often used without guarantees regarding project legality, contract structure, or financial capacity, thereby generating gharar, misrepresentation, and risk shifting to consumers. The article proposes a three pillar Sharia label: certification design legal verification, Sharia audit, and financial oversight, implemented by competent authorities as a prerequisite for using the Sharia label in promotion; absent such certification, Sharia claims should be treated as misleading information and unlawful advertising, subject to administrative sanctions and civil liability under the consumer protection framework